2019
DOI: 10.1002/lt.25444
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Simultaneous Liver‐Kidney Transplantation in the United States

Abstract: On August 10, 2017, a formal policy was enacted in the United States that defined listing criteria for simultaneous liver‐kidney transplantation and priority for patients who received a liver transplantation (LT) and subsequently developed significant kidney disease after LT. This article reviews and summarizes the rationale for such policies, the policies themselves, and the potential impact on LT candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
(41 reference statements)
0
23
0
3
Order By: Relevance
“…Причем формирование рено-портальной транспозиции является предпочтительным методом, поскольку при успешном выполнении сопряжено с меньшим количеством осложнений [1,14]. Однако эти методики большинством исследователей считаются наиболее сложными, связанными с высокой заболеваемостью и риском смерти реципиента в раннем послеоперационном периоде в случае неполной коррекции существующей портальной гипертензии, приводящей к скорой дисфункции печеночного графта [2][3][4][5][6][15][16][17]. Для достижения удовлетворительных результатов пациенты должны быть направлены в специализированные центры, хирургическая стратегия должна быть тщательно спланирована до трансплантации, могут потребоваться высокотехнологичные сосудистые вмешательства, в ряде случаев -индивидуальная техника трансплантации, не имеющая аналогов в мире [5,14,18,19].…”
Section: обзор литературыunclassified
See 1 more Smart Citation
“…Причем формирование рено-портальной транспозиции является предпочтительным методом, поскольку при успешном выполнении сопряжено с меньшим количеством осложнений [1,14]. Однако эти методики большинством исследователей считаются наиболее сложными, связанными с высокой заболеваемостью и риском смерти реципиента в раннем послеоперационном периоде в случае неполной коррекции существующей портальной гипертензии, приводящей к скорой дисфункции печеночного графта [2][3][4][5][6][15][16][17]. Для достижения удовлетворительных результатов пациенты должны быть направлены в специализированные центры, хирургическая стратегия должна быть тщательно спланирована до трансплантации, могут потребоваться высокотехнологичные сосудистые вмешательства, в ряде случаев -индивидуальная техника трансплантации, не имеющая аналогов в мире [5,14,18,19].…”
Section: обзор литературыunclassified
“…Высокий профессиональный уровень специалистов-трансплантологов обеспечивает возможность выполнения сложных симультанных трансплантаций, когда имеющиеся сосудистые осложнения, такие как тотальный тромбоз воротной вены, без проведения высокотехнологичных сосудистых реконструкций являются абсолютными противопоказаниями к трансплантации по причине бесперспективности восстановления нормальной перфузии графта, нарушения функции и приживления пересаженного органа в посттрансплантационном периоде [1,2]. Эти методики большинством исследователей считаются наиболее сложными, связанными с высокой заболеваемостью и риском смерти реципиента в раннем послеоперационном периоде [2][3][4][5][6]. Описаны единичные случаи успешно выполненных операций подобного типа с благоприятным долгосрочным прогнозом по данным ведущих мировых центров трансплантации [7].…”
Section: Introductionunclassified
“…The etiology of renal dysfunction varies and can be related to reversible causes, such as prerenal azotemia and hepatorenal syndrome (HRS), or irreversible etiologies, such as advanced diabetic nephropathy. Differentiating between reversible and irreversible causes of renal dysfunction can be challenging, potentially leading to unnecessary simultaneous liver‐kidney transplantation (SLKT) . Previous studies indicated that some SLKT recipients recover native kidney function shortly after transplantation, whereas other patients develop end‐stage renal disease within 1 year from LT .…”
mentioning
confidence: 99%
“…Differentiating between reversible and irreversible causes of renal dysfunction can be challenging, potentially leading to unnecessary simultaneous liver‐kidney transplantation (SLKT) . Previous studies indicated that some SLKT recipients recover native kidney function shortly after transplantation, whereas other patients develop end‐stage renal disease within 1 year from LT . Identifying the cause of renal dysfunction is particularly vexing when information regarding baseline renal function is lacking and in patients presenting with renal dysfunction and risk factors for chronic kidney disease (CKD), including diabetes mellitus (DM) and hypertension, who present with concomitant hematuria and/or proteinuria.…”
mentioning
confidence: 99%
See 1 more Smart Citation